2017
DOI: 10.1017/jfm.2017.732
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of multicomponent droplet dissolution in a sparingly miscible liquid

Abstract: The dissolution of a multicomponent nanodrop in a sparingly miscible liquid is studied by molecular dynamics (MD) simulations. We studied both binary and ternary systems, in which nanodroplets are formed from one and two components, respectively. Whereas for a single-component droplet the dissolution can easily be calculated, the situation is more complicated for a multicomponent drop, as the interface concentrations of the drop constituents depend on the drop composition, which changes with time. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Note that not only the dissolution of sessile binary droplets with the resulting Marangoni flows is highly non-trivial, as elaborated above, but even the dissolution of spherical binary droplets in the bulk: The reason is that, due to selective dissolution, concentration gradients inside the droplet between its surface and its bulk can arise [144]. These can lead to considerable memory effects (in particular for small droplets), which do not exist for the dissolution of a pure droplet [144][145][146].…”
Section: Droplets In Concentration Gradients Emerging From Phase Tranmentioning
confidence: 99%
“…Note that not only the dissolution of sessile binary droplets with the resulting Marangoni flows is highly non-trivial, as elaborated above, but even the dissolution of spherical binary droplets in the bulk: The reason is that, due to selective dissolution, concentration gradients inside the droplet between its surface and its bulk can arise [144]. These can lead to considerable memory effects (in particular for small droplets), which do not exist for the dissolution of a pure droplet [144][145][146].…”
Section: Droplets In Concentration Gradients Emerging From Phase Tranmentioning
confidence: 99%
“…Conversely, using molecular dynamics simulations, Lohse et al demonstrated that dissolved gas was one of the conditions required for nucleation of a NB and investigated its impact on the NP growth dynamics. 88 The authors found that dissolved gas above a certain threshold concentration could dramatically facilitate vapor NB nucleation due to the formation of gaseous weak spots in the surrounding liquid.…”
Section: Light-direct-responsive Nbsmentioning
confidence: 99%
“…They employed thermodynamic equilibrium constraints at the interface with the adoption of the UNIQUAC model, which is frequently applied in the description of phase equilibria. Molecular dynamics simulations were performed by Maheshwari et al (2017) with the conclusion of the importance of the interaction between the drop constituents and the host liquid during multicomponent drop dissolution. All these studies focus on the investigation of pure diffusion processes.…”
Section: Introductionmentioning
confidence: 99%